Development of an in-vitro model for extracorporeal blood pumps to study the effects of artificial pulsatility on human blood - Zieger, Barbara; Schneider, Denise; Brixius, Sam Joé; Scherer, Christian; Buchwald, Armin; Trummer, Georg; Czerny, Martin; Beyersdorf, Friedhelm; Busch, Hans-Jörg; Benk, Christoph; Pooth, Jan-Steffen (Frontiers in Medicine, 2023)
Introduction The application of extracorporeal circulation (ECC) systems is known to be associated with several implications regarding hemolysis, inflammation, and coagulation. In the last years, systems with pulsatile blood flow are increasingly used with the intention to improve hemodynamics in reperfusion. However, their implications on the aforementioned aspects remain largely unknown. To investigate the effects of pulsatility, this ex-vivo study was initiated. Methods Test circuits (primed with human whole blood) were set up in accordance with the recommendations of international standards for in-vitro evaluation of new components and systems of ECC. Diagonal pumps were either set up with non-pulsatile (n=5, NPG) or pulsatile (n=5, PG) pump settings and evaluated for six hours. All analyses were conducted with human whole blood. Blood samples were repeatedly drawn from the test circuits and analyzed regarding free hemoglobin, interleukin 8 (IL-8), platelet aggregation and acquired von Willebrand syndrome (AVWS). Results After one hour of circulation, a significant coagulation impairment (impaired platelet function and AVWS) was observed in both groups. After six hours of circulation, increased IL-8 concentrations were measured in both groups (NPG: 0.05 ± 0.03 pg/mL, PG: 0.03 ± 0.01 pg/mL, p=0.48). Pulsatile pump flow resulted in significantly increased hemolysis after six hours of circulation (NPG: 37.3 ± 12.4 mg/100L; PG: 59.6 ± 14.5 mg/100L; p<0.05). Conclusion Our results indicate that the coagulative impairment takes place in the early phase of ECC. Pulsatility did not affect the occurrence of AVWS ex-vivo. Prolonged durations of pulsatile pump flow led to increased hemolysis and therefore, its prolonged use should be employed cautiously in clinical practice with appropriate monitoring.